2017
DOI: 10.1016/j.immuni.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of the Cytokine GM-CSF Induces Spontaneous Phagocyte Invasion and Immunopathology in the Central Nervous System

Abstract: Chronic inflammatory diseases are influenced by dysregulation of cytokines. Among them, granulocyte macrophage colony stimulating factor (GM-CSF) is crucial for the pathogenic function of T cells in preclinical models of autoimmunity. To study the impact of dysregulated GM-CSF expression in vivo, we generated a transgenic mouse line allowing the induction of GM-CSF expression in mature, peripheral helper T (Th) cells. Antigen-independent GM-CSF release led to the invasion of inflammatory myeloid cells into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
113
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(121 citation statements)
references
References 44 publications
7
113
0
1
Order By: Relevance
“…Previous studies showed that GM-CSF overexpression resulted in an increase in both Ly6G + granulocytes and monocytic myeloid cells (14, 29). Nevertheless, we observed that increase in monocytic myeloid cells in GMtg mice was greater than increase in granulocytes in spleen (Figures 1C–G).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies showed that GM-CSF overexpression resulted in an increase in both Ly6G + granulocytes and monocytic myeloid cells (14, 29). Nevertheless, we observed that increase in monocytic myeloid cells in GMtg mice was greater than increase in granulocytes in spleen (Figures 1C–G).…”
Section: Resultsmentioning
confidence: 99%
“…Apart from spleen, there was a greater increase in monocytic myeloid cells in blood (Supplementary Figure 1B), lung (Supplementary Figure 1B) and liver (Supplementary Figure 1C). As Ly6C can be downregulated on monocytes/macrophages under high levels of GM-CSF (14, 29), expression of CCR2 reporter we also used to aid identification of monocytic myeloid cell subsets. When monocytic cells were further separated into CCR2 + (either Ly6C hi and Ly6C lo ) and Ly6C − CCR2 − cells, increase in CCR2 + cells in GMtg mice was more prominent (Supplementary Figures 1A–C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In EAE, GM-CSF production by Th17 cells activates effector mononuclear phagocytes (89). GM-CSF-activated mononuclear phagocytes that migrate into the CNS exhibit a more pathogenic signature than those that migrate to other organs, which may be due to the unique CNS microenvironment (61).…”
Section: Gm-csf Gm-csf Stimulates Bmd Stem Cells To Differentiate Inmentioning
confidence: 99%
“…In this issue of Immunity , Spath et al show that the dysregulated production of GM-CSF rather than IL-17 induces spontaneous immunopathology in a mouse model of CNS inflammation. …”
mentioning
confidence: 98%